2017
DOI: 10.1051/matecconf/201710402005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drag and lift in the internal flow field of a dual rotor spinning unit via CFD

Abstract: In the present study, we evaluate the drag and lift magnitude in the new dual-feed rotor spinning unit using computational fluid dynamics technique. We adopt theoretical and numerical approach based on FLUENT to investigate the influence of new design on the drag and lift in the rotor interior. Results reveal that the drag and lift inside the rotor of the proposed model are reduced by 60-80% and 50-66% respectively as compared to the conventional unit. The velocity and pressure profiles become evenly distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It is concluded that the air extraction provides the necessary negative pressure conditions for fiber transportation, and the rotating mechanism facilitates fiber alignment and transfer to the sliding surface and accumulation groove. Akankwasa et al 22 analyzed the lift and drag forces exerted on the fibers by the flow field through the flow velocity, and concluded that the improvement in internal flow field stability was due to a decrease in lift and drag forces.…”
Section: Vortex Fieldsmentioning
confidence: 99%
“…It is concluded that the air extraction provides the necessary negative pressure conditions for fiber transportation, and the rotating mechanism facilitates fiber alignment and transfer to the sliding surface and accumulation groove. Akankwasa et al 22 analyzed the lift and drag forces exerted on the fibers by the flow field through the flow velocity, and concluded that the improvement in internal flow field stability was due to a decrease in lift and drag forces.…”
Section: Vortex Fieldsmentioning
confidence: 99%